Peningkatan Kualitas Pelayanan Terhadap Kepuasan Pelanggan dengan Metode Servqual di PT. Tiki Jalur Nugraha Ekakurir - Ikhwana, Andri; Nurhamdani, Farhan (Jurnal Kalibrasi, 2023)
Service quality is one of the important factors for logistics service companies in providing quality services to their consumers. Logistics service companies aim to provide goods delivery services from producers to consumers. PT Tiki Lane Nugraha Ekakurir is a company operating in the logistics services sector. There is a decrease in service use and a change in market share dominance which was previously dominated by companies, so it is proposed to improve service quality based on customer satisfaction. This research aims to describe the quality of service that occurs in the company along with the priority order for service improvement. This research uses servqual, importance performance analysis (IPA) and potential gain in customer value (PGCV). The servqual method is used to determine gaps between perceptions and expectations, the importance performance analysis method is used to map and identify indicators of service quality that must be improved, while the potential gain in customer value method is used to determine the priority order of services that must be improved. The results of research using the IPA method showed that there were six indicators in quadrant A as the focus for improving service quality accompanied by a priority order of services that must be improved using the PGCV method and a service improvement plan was carried out for each indicator in quadrant A.